Sporotrichosis: an update on epidemiology and in vitro antifungal susceptibilities of Sporothrix schenckii isolated from humans and cats in Klang Valley, Malaysia - Selvarajah, Gayathri Thevi; Santhanam, Jacinta; Mah, Elizebeth; James, Jasper Elvin; Abdul Razak, Mohd Fuat; Selvakumar, Raja Rajeswari; Al-Shaibani, Muhanna M. (Universiti Putra Malaysia Press, 2024)
The epidemiological pattern of human sporotrichosis infections in Klang Valley, Malaysia and antifungal susceptibility of the causative fungal pathogen, Sporothrix schenckii was determined. A total of 67 culture positive sporotrichosis cases were recorded from 2015-2018 at three Klang Valley hospitals, with a majority in the 19-30 years age group. Association with felines represent the highest (47.76%) risk factor for sporotrichosis. The clinical presentation was predominantly lymphocutaneous infection (59.67%). S. schenckii isolates from humans and cats were tested for antifungal susceptibility using the standardized broth microdilution method. All 25 S. schenckii isolates tested were susceptible to itraconazole (MIC 0.5-2 μg/mL), while MIC was lower for ravuconazole (0.125-1 μg/mL). Awareness and emphasis on feline associated sporotrichosis are needed in Malaysia. While itraconazole is the recommended treatment, ravuconazole may be an additional, potentially effective treatment against S. schenckii.